1998
DOI: 10.1080/10934529809376748
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of glycerol trinitrate by activated sludge: Cosubstrate requirements, inhibition, and kinetics

Abstract: Nitroglycerin or glycerol trinitrate (GTN) is an energetic and toxic substance with a wide range of military and pharmaceutical applications. Studies conducted with activated sludge showed that GTN is amenable to aerobic degradation only in the presence of a primary carbon source, such as glucose.Kinetic experiments indicated that GTN is an inhibitory substrate whose presence during biodegradation, reduces substantially the microbial yield and the apparent maximum specific growth rate coefficient of primary su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although the addition of calcium sulfate produced similar mineralization extents after 24 days, longer incubations (42 days) revealed that controlled-release nitrate has a greater enhancement of the anaerobic biodegradation (Figure C). This observation can be explained for two reasons: (a) controlled-release of nitrate benefits facultative microbes or nitrate reducers, which have the pathways to use higher free energy nitrate and (b) nitrocellulose provides not only the electron acceptors but also carbon and nitrogen sources (which could eventually become limiting in a closed system) and thus helps improve the biodegradation activity of sulfate reducers as well ( , ).
2 Effect of different added electron acceptors on the extent of anaerobic biodegradation ( 14 CO 2 recovery) as a function of depth intervals for n = 2.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the addition of calcium sulfate produced similar mineralization extents after 24 days, longer incubations (42 days) revealed that controlled-release nitrate has a greater enhancement of the anaerobic biodegradation (Figure C). This observation can be explained for two reasons: (a) controlled-release of nitrate benefits facultative microbes or nitrate reducers, which have the pathways to use higher free energy nitrate and (b) nitrocellulose provides not only the electron acceptors but also carbon and nitrogen sources (which could eventually become limiting in a closed system) and thus helps improve the biodegradation activity of sulfate reducers as well ( , ).
2 Effect of different added electron acceptors on the extent of anaerobic biodegradation ( 14 CO 2 recovery) as a function of depth intervals for n = 2.
…”
Section: Resultsmentioning
confidence: 99%
“…The initial extraction of 1 g of nitrocellulose in 100 mL of water provides 0.29 mM nitrate in solution ( , ). Under anaerobic conditions, nitrocellulose can be degraded to nitrate, nitrite, sugar, H + , and NH 4 + that can be used by bacteria as electron acceptors and carbon sources ( , ).
1 Molecular structure of nitrocellulose (C n H 7/6 n O 11/6 n N 1/2 n , cellulose nitrate).
…”
Section: Introductionmentioning
confidence: 99%